Improving Community Health Workers’ Knowledge in Early Stunting Detection Through Anthropometric Training and The Beraksi Application - Dyeri Susanti; Selvi Putri Octaviani; Tazkihatun Nufush (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
Stunting remains a critical public health issue that impairs child growth and development. In Cibeber sub-district, 6.83% of the total 1,339 preschool‐aged children were stunted, with the highest rates observed in RW 08 (38 children), RW 06 (32), and RW 03 (22). According to Indonesian Ministry of Health Regulation No. 2/2020, stunting is defined as a height-for-age z-score below –2 SD. This study aimed to evaluate whether anthropometry training using the mobile application BERAKSI can improve community health workers’ knowledge of early stunting detection. Employing a descriptive quantitative design with a pre-test–post-test, we involved all 18 community health workers from Posyandu Rose A and B in RW 08, Cibeber. Pre-training, 56% (10) of community health workers demonstrated good knowledge, 33% (6) fair, and 11% (2) poor. Post-training, all community health workers (100%) achieved good knowledge. The findings indicate that comprehensive anthropometry training, combined with application-based guidance, significantly enhances community health workers’ knowledge. For accurate growth surveillance and record keeping in maternal–child health books, community health workers must possess standardized anthropometric skills and proficiency.